THE EFFECT OF ECONOMIC LITERATURE, PARENTS' INCOME AND LIFESTYLE ON THE PRODUCTIVE BEHAVIOR OF SMAN 10 PEKANBARU STUDENTS - Rezky Rahmadani; Sumarno Sumarno; Gusnardi Gusnardi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This study aims to analyze the effect of Economic Literacy, Parents' Income and Lifestyle on Productive Behavior. The data used consists of primary data. The data was collected using a questionnaire. The population of the study was 358 students of class X MIPA and IPS majors with 189 samples taken. The analytical method used was path analysis. The results showed that Economic Literacy was proven to have a significant effect on Productive Behavior, then the parental income variable had no effect on Productive Behavior, and Lifestyle had a significant effect on Productive Behavior. Overall Economic Literacy, Parents' Income and Lifestyle have an effect on Productive Behavior with a contribution rate of 74.8% and the rest is influenced by other factors.